2012
DOI: 10.1155/2012/173793
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Bilateral Progressive Rheumatoid Corneal Melt with Infliximab

Abstract: Purpose. To report the use of infliximab in the rapid stabilization of a case of progressive, bilateral rheumatoid peripheral ulcerative keratitis (PUK) that failed to respond to conventional immunosuppressive therapy. Methods. A single interventional case report. Results. A patient with rheumatoid arthritis presented with bilateral PUK following a 2-month history of ocular discomfort and redness. His systemic prednisolone (PDN) and methotrexate (MTX) were increased and, despite an initial favorable response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Thomas JW et al demonstrated that Infliximab was effective in three patients with PUK related to RA that was refractory to conventional treatments as it stopped the corneal thinning, reduced the conjunctival inflammation and closed the corneal epithelial defect [26]. Antao SF et al described the efficacy of Infliximab used at the dose of 5 mg/kg due to the advanced severity of the case by the stabilization of bilateral active corneal melts resistant to all conventional therapies, leading the disease progression to stop after multiple bilateral tectonic keratoplasties [27]. In a few published cases, Infliximab has proved to be the optimal option in refractory cases of RA associated scleritis and PUK [4,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Thomas JW et al demonstrated that Infliximab was effective in three patients with PUK related to RA that was refractory to conventional treatments as it stopped the corneal thinning, reduced the conjunctival inflammation and closed the corneal epithelial defect [26]. Antao SF et al described the efficacy of Infliximab used at the dose of 5 mg/kg due to the advanced severity of the case by the stabilization of bilateral active corneal melts resistant to all conventional therapies, leading the disease progression to stop after multiple bilateral tectonic keratoplasties [27]. In a few published cases, Infliximab has proved to be the optimal option in refractory cases of RA associated scleritis and PUK [4,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases reported in the literature describe PUK as the cause of corneal perforations. [ 1 2 3 4 5 6 ] PUK causes local vasculitis and thinning of the cornea that can lead to perforation, which can be debilitating and recurrent. [ 2 ] However, the pathophysiology is not very well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, phacoemulsification surgery with intraocular lens implantation in the posterior chamber was performed 9 months after keratoplasty and the initiation of infliximab treatment. There was no problem during or after surgery (76). Adalimumab is a humanized recombinant IgG1 monoclonal antibody that targets TNF-alpha.…”
Section: B) Treatmentmentioning
confidence: 99%